Независимый библиотечный адвокат: [юридический сборник-журнал (главный редактор О. Бойкова]) - Бойкова Ольга Феоктистовна (2010)
Экземпляры: КХ (20100715) / Инвентарный номер: 1080075 / Сис.шифр: 78.34(2) / Авт.знак: Н 44 / ГРНТИ: 10 / ББК: 78.34к1